On holding the XVI meeting of Coordinating Councel on Sanitary Protection of the Territory of the Memeber-States of the CIS from Importation and Spread of Particularly Dangerous Infectious Diseases - Article Editorial (Проблемы особо опасных инфекций, 2022)
.